Gender‐ and site‐specific differences of colorectal neoplasia relate to vitamin D. Issue 11 (2nd October 2014) - Aigner, E.; Stadlmayr, A.; Huber‐Schönauer, U.; Zwerina, J.; Husar‐Memmer, E.; Niederseer, D.; Trauner, M.; Heuberger, A.; Hohla, F.; Schett, G.; Patsch, W.; Datz, C.
Summary: Background: The effect of vitamin D on colorectal adenomas may vary with regard to gender, localisation and histological type of the lesion. Aim: To define the role of vitamin D and gender in a Caucasian cohort of subjects undergoing screening colonoscopy after consideration of established risk factors. Methods: One thousand five hundred and thirty‐two subjects (813 males, 58.8 ± 9.7 years; 719 females, 59.7 ± 10.7 years) were allocated to tertiles of 25‐hydroxyvitamin D3 [25(OH)D3 ] serum concentrations. The number, localisation, size and histology of the detected colonic lesions were recorded. Results: Among men, no association was found between vitamin D and the total number, size and histological stage of adenomas at any site. In female subjects, less women with adenomas were found in the highest vitamin D tertile ( N  = 42/239; 17.2%) as compared to the low vitamin D group ( N  = 60/240; 25.0%; P  = 0.035). In particular, the number of women with adenomas in the proximal colon was significantly lower in the highest tertile ( N  = 21/239, 8.8%) compared to the low vitamin D group ( N  = 41/240; 17.1%; P  = 0.007). The rates at other sites were not different. The inverse association of vitamin D serum concentrations with the presence of adenomas in the proximal colon was maintained after adjustment for potential confounders. In 80 women on vitamin D supplementation, the rate of adenomas was lower compared to those not on supplementation (3/80; 3.8%; vs. 90/719; 12.5%; P  = 0.016). Conclusions: A potential preventive effect of vitamin D on colorectal adenomas was found in the proximal colon in women. This observation is supported by further decrease of lesions in the proximal colon of women on vitamin D supplementation.